Consulting report Team 2- MASEDI Contratistas Generales - Bayer, Sofie Barbara (2020)
MASEDI is a Peruvian construction company created and founded by Vladimir Sokolic in 1999. They provide services in the field of architectural design, construction, maintenance and everything related to the area. Its approach as a company is based on leadership, experience, quality and personalized service in each project. The main problem identified is the low brand awareness which prevents from obtaining a greater number of clients in the private sector. This is mainly due to the strong competition, lack of a marketing department to promote the brand, as well as the reliance on word of mouth advertising thanks to its good reputation in the public sector. In that sense, the CEO is interested in finding strategies to make MASEDI recognized in the private sector for its quality service and expertise. The theory reviewed to develop the solution to the problem suggests marketing strategies through social media and content management; customer relationship management (CRM); and corporate social responsibility activities (CSR). Then, four alternatives were developed and evaluated regarding to cost, feasibility, effectiveness, ease of implementation and reliability. The final proposal includes an integrated marketing communication strategy through digital and nondigital media, as well as the division of the client portfolio, whose implementation plan is detailed step by step for MASEDI, in order to obtain new clients, get brand recognition and increased traffic on the web and social networks.